New Concepts in Family Research and Their Application to Families and Migration - Seymour , Julie (Vilnius University Open Series, 2020)
The chapter provides a conceptual framework in which to understand empirical data on families and migration. By focusing on the family, rather than the individual in migration research, theories and concepts from family and childhood studies can explain the experiences of the wider group of people who are involved in, and impacted by migration. The chapter shows how viewing the family as involved a process of dynamic family practices allows the data in this book to reveal the engaged and committed ways that people conduct their family life despite being separated by long distances.
Keywords: Family practices; childhood studies; personal life; generagency; migration research